Proteomic profiling of neonatal herpes simplex virus infection on dried blood spots - Kia Hee Schultz Dungu; Christian Munch Hagen; Marie Bækvad-Hansen; Victor Yakimov; Alfonso Buil Demur; Emma Malchau Carlsen; Nadja Hawwa Vissing; Tine Brink Henriksen; Trine Hyrup Mogensen; David Michael Hougaard; Ulrikka Nygaard; Jonas Bybjerg-Grauholm (Communications Medicine)
Abstract Background: Neonatal herpes simplex virus (HSV) infection is life-threatening, with a mortality of up to 70–80% when disseminated, often due to vague symptoms and delayed treatment. Neonatal screening using dried blood spot (DBS) samples is among the most impactful preventative health measures ever implemented, but screening for HSV has not been investigated. Methods: We investigated high throughput multiplexed proteomics on DBS samples collected on days 2–3 of life from a nationwide cohort of neonates with HSV infection (n = 53) and matched controls. We measured 2941 proteins using the Olink Explore 3072 panels and proximity extension assays, followed by differential protein expression by Analysis of Variance with post-hoc correction and functional annotation. Results: Here, we show distinct protein profiles in neonates with disseminated HSV disease, with differences in 20 proteins compared to controls. These proteins are associated with innate and adaptive immune responses and cytokine activation. Conclusions: Our findings indicate the potential of neonatal screening for disseminated HSV disease to ensure early treatment and reduce the high mortality.